Pendampingan dan Pengembangan Identitas Visual untuk UMKM Limasan’s Finest di Kabupaten Sumedang - I Gusti Agung Rangga Lawe; I Dewa Alit Dwija Putra; Dimas Krisna Aditya; Catrine; Tasya Marlyah Yasmin (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Sumedang Regency is a regency in West Java with potential for UMKM development. One of the UMKMs operating in the culinary sector in Sumedang Regency is Limasan's Finest. This restaurant, which carries the theme of traditional food, has two sub-brands named Kinca Ipung and Nose Radar. However, there is a problem where Limasan's Finest does not yet have a complete and consistent visual identity. This issue can be seen from the existence of two completely different menu book designs. For this reason, the community service team provided assistance and developed a new visual identity for this restaurant. The implementation method consisted of an initial survey process, observation, visual identity design, menu book and uniform design, printing, and submission of the results. A total of eight employees, including the restaurant owner, received guidance on the importance of visual identity for a restaurant. The result of the visual identity development is a new logo with a stronger design and a color palette that aligns with the restaurant's philosophy. Both are applied to the menu book design and employee uniforms. In the future, the team will try to collaborate again with Limasan's Finest in developing its new visual identity into other media such as signage, social media, and restaurant interior decorations.